Magnesium Sulfate Therapy’s Effects on GCS Scores in Patients with Severe TBI - Saqib Khalil, Badar Uddin Ujjan, Mian Ayaz Ul Haq, Hafiz Fahad Ullah Saeed, Fayaz Ahmed Memon, Sangeet (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The main purpose of this study is to examine whether or not magnesium sulphate improves the Glasgow Coma Scale (GCS) scores of individuals who have suffered severe traumatic brain injury. Study Design: Prospective study Place and Duration: Women medical college Abbottabad and Department of Neurology Hayatabad Medical Complex, during from Jan, 2021 to June, 2021. Methods: This research includes 72 participants of both sexes. Patients were between the ages of 18 and 55 when they were enrolled. All the patients had severe traumatic brain injury and magnesium sulphate treatment was administered to each patient. All of the patients’ demographic information was obtained after they signed an informed permission form. In this study, the Glasgow coma score (GCS) was measured on the first and forth days of hospitalization, respectively. The SPSS 20.0 version was used to analyze all of the data. Results:Amon 73 included patients,males were higher in numbers 41 (56.9%) than females 31 (43.1%). Presented patients had mean age 43.6±9.39 years and had mean BMI 25.8±12.83 kg/m2 . Post traumatic mean time of brain injury was 6.16 ±4.41 hours. At first day without magnesium sulfate mean GCS of the patients was 7.3±8.30 but at the 4th day GCS was 11.9±6.42 with p value < 0.04. GCS, on the other hand, showed no significant differences between gender and illness duration. Conclusion: The results of this study led us to the conclusion that the use of magnesium sulphate was an effective method for treating traumatic brain injury in patients. GCS was improved among patients when magnesium sulphate was administered on the seventh day.